National Central Banking and the International Economy - Triffin, R. (Review of Economic Studies, 1946)
Journal Article National Central Banking and the International Economy Get access R. Triffin R. Triffin Washington Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 14, Issue 2, 1946, Pages 53–75, https://doi.org/10.2307/2296086 Published: 01 September 1946